Financial Management and Investment Management For Shipping School Cadets - Sukiswo, Helmy; Widodo, Ulfa Puspa; Azmiyanti, Rizdina (Jurnal Pengabdian Masyarakat Akademisi, 2024)
Financial management and investment management are very important aspects in the life of shipping school cadets who aim to become professionals in the maritime industry. This article discusses dedication efforts aimed at providing them with a practical understanding of wise financial management and smart investment management. Through a practical approach and relevant case studies, this article seeks to equip them with strong financial skills to plan for a financially stable future, while encouraging awareness of the importance of financial education among shipping schools and other maritime educational institutions.